Rare case of hypothyroidism in a child - Tatyana V. Kovalenko; Irina N. Petrova; Liaisan M. Mullakhmetova (Клинический разбор в общей медицине)
Hypothyroidism is a decrease or complete loss of thyroid function. In childhood, congenital hypothyroidism is the most common, which can be either permanent or transient. One of the reasons for the development of hypothyroidism in newborns may be the mother's intake of large doses of iodine during pregnancy and, as a consequence, the occurrence of the Wolf–Chaikoff phenomenon to prevent the synthesis of large amounts of thyroid hormones by the thyroid gland of the fetus and newborn. We present a clinical observation of a rare form of hypothyroidism with goiter in a child born to a mother who took narcotic drugs containing large doses of iodine. In the presented observation, hypothyroidism was transient in nature; a feature of the disease was a long-lasting enlargement of the thyroid gland. Taking into account that even a temporary decrease in the level of thyroid hormones can negatively affect the neuropsychic development of the child, the newborn patient was prescribed replacement therapy with levothyroxine sodium at a dose of 25 mcg/day. The patient's long-standing goiter served as the reason for prolonging replacement therapy until the age of 1 year and subsequent resumption of therapy twice until the volume of the thyroid gland normalized.